TESTES EM VENTILADORES CENTRÍFUGOS PARA UTILIZAÇÃO EM TRANSPORTE PNEUMÁTICO DE GRÃOS - Valdiero, Antonio C.; Hoffmann, Roger S.; Bortolaia, Luís A.; Santos, Felipe L. d.; Dryer, Fernanda J. (Salão do Conhecimento, 2013)
Resumo